Resin composition, resin layer, laminate and container
A resin composition with controlled molecular weight distribution addresses the challenges of dispersibility and physical properties in containers by enhancing inorganic particle dispersibility, improving impact resistance, moldability, and heat resistance, while being environmentally friendly.
Patent Information
- Application Number
- JP2024099598
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2024-03-08
- Filing Date
- 2024-06-20
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Conventional resin compositions used in containers face challenges in achieving high dispersibility of inorganic particles, leading to reduced impact resistance, moldability, and heat resistance, especially at extreme temperatures, while also being environmentally friendly.
A resin composition with controlled molecular weight distribution, characterized by a differential molecular weight distribution curve with specific peak top and half-width ranges, is used to enhance the dispersibility of inorganic particles, allowing for increased inorganic particle content and reduced resin component content, thereby improving impact resistance, moldability, and heat resistance.
The resin composition achieves excellent dispersibility and physical properties, including improved impact resistance at low temperatures, moldability, and heat resistance, while being environmentally friendly by reducing resin content and increasing inorganic particle content.
Smart Images

Figure 0007616729000001_ABST
Abstract
Description
[Background technology]
[0001] Resin molded containers are used as containers for various liquid or solid products, including food packaging, beverages, cooking oils, precision instruments, stationery, industrial products such as screws and nuts, detergents, shampoos, seasonings, etc. (For example, Patent Document 1) This is because resins can be easily molded into required shapes and have the property of high chemical and physical durability.
[0002] Furthermore, in order to achieve sufficient rigidity and strength required for food containers, studies have been conducted on making the heat insulating base material layer in the laminate sheet out of a specific resin composition (Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 08-244747 [Patent Document 2] Patent Publication No. 2021-37748 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention aims to provide a resin composition, a resin layer, a laminate, and a container that have excellent dispersibility of inorganic particles and that satisfy physical requirements (moldability, impact resistance, heat resistance) for containers and the like that use the resin composition, by using a resin component with controlled molecular weight distribution. [Means for solving the problem]
[0005] As a result of extensive investigations aimed at solving the above problems, the present inventors provide the following [1] to [6]. [1] A resin composition comprising one or more resin components and one or more inorganic particles, wherein in a differential molecular weight distribution curve of the resin components as determined by gel permeation chromatography (GPC), the half-value width of a peak having a peak top between 4.5 and 6.5 is 0.90 or more and 2.00 or less. [2] A resin layer using the resin composition according to [1]. [3] A laminate comprising the resin layer according to [2] and one or two surface layers. [4] A container comprising the resin layer described in [2]. [5] A container comprising the laminate described in [3]. [6] An article containing a container and contents as described in [4] or [5]. Effect of the Invention
[0006] According to the present invention, by using a resin component with a controlled molecular weight distribution, it is possible to provide a resin composition, a resin layer, a laminate, and a container which have excellent dispersibility of inorganic particles and which satisfy physical requirements (moldability, impact resistance, heat resistance) for containers and the like using the same. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram of a laminate of the present embodiment including one surface layer 120. FIG. [Diagram 2] FIG. 1 is a conceptual diagram relating to a method for producing a resin composition, a resin layer, a laminate, a container, and an article according to the present embodiment (an example in which a master batch is not used). [Diagram 3] FIG. 1 is a conceptual diagram relating to a method for producing a resin composition, a resin layer, a laminate, a container, and an article according to the present embodiment (an example in which a master batch is used). [Figure 4] FIG. 1 is a conceptual diagram of how to determine a half-value width. [Diagram 5] 1 is a schematic diagram of a laminate of the present embodiment including a surface layer 121 and a surface layer 122. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The above-mentioned Patent Document 1 describes an invention related to a resin bottle having a specific layer structure. However, although the invention describes the provision of shape retention to this resin bottle, it does not consider the improvement of dispersibility of inorganic particles or impact resistance.
[0009] Although Patent Document 2 describes a laminated sheet containing only 20% talc as an inorganic filler, the effect of using a resin composition having a specific molecular weight distribution is not examined.
[0010] Currently, resin compositions used for containers and the like are required to improve physical requirements (moldability, impact resistance, heat resistance, etc.) while taking the environment into consideration. Environmentally friendly resin compositions are required to increase the content of inorganic particles in order to reduce the content of resin components in the resin composition. By increasing the content of inorganic particles, the heat resistance of a resin layer using a resin composition can be improved, but the upper limit of the content is limited due to low dispersibility in the resin components. It is also known that as the content of inorganic particles increases, the moldability and impact resistance decrease, and the moldability when molding the resin layer into a container decreases.
[0011] Recently, there is a strong demand for the content of the resin component to be 50.0% by mass or less in the resin composition, but to achieve this, it is difficult to uniformly disperse inorganic particles in the resin using only the resin components that have been used up to now, and even if this is achieved, the impact resistance is greatly reduced and the moldability is also reduced. If the impact resistance is low, the container will be damaged during transportation or storage, and if the contents are liquid, there will be a risk of leakage. In addition, when the contents are precision machinery such as a central processing unit (CPU), impact resistance is required to protect the CPU from external impact, but there are problems such as the inability to meet the required characteristics.
[0012] In the present disclosure, "impact resistance" refers to the performance of a container, etc., not causing or suppressing damage to the container, etc., when the container, etc., is dropped. By preventing the container from being damaged, damage to the contents is suppressed.
[0013] In the present disclosure, “heat resistance” refers to the ability to retain the shape of a container at high temperatures after it has been made into a container; for example, in the case of a food container, it refers to the property that the shape of the container changes little even when heated to high temperatures in a microwave oven or the like.
[0014] In the present disclosure, "moldability" means that the temperature and pressure range when a container or the like is manufactured using the resin composition is wide and within a range that can be achieved by normal manufacturing equipment, and that the physical properties of the resin composition do not change at the temperature and pressure, the fluidity of the resin composition is suitable for injection molding, and the shrinkage rate is small. For the resin composition of the present embodiment, it is important that the temperature and pressure during molding are within an appropriate range, and that the shrinkage rate after manufacturing the laminate or container is small.
[0015] When conventional resin compositions were used, the decrease in impact resistance was particularly noticeable at extremely low temperatures of -20°C or below. When used as a tray for frozen foods or the like, it is necessary to protect the contents inside the freezer, and when used as a container for transporting precision equipment, it is necessary to have impact resistance at the extremely low temperatures of the cargo hold during transportation as air cargo. For these reasons, there has been a demand for a resin composition that satisfies the requirements for physical impact resistance while reducing the content of resin components.
[0016] It has been found that the resin composition of the present disclosure uses a resin component with a controlled molecular weight distribution, thereby improving the dispersibility of inorganic particles, increasing the content thereof, and reducing the content of the resin component in the resin composition, while providing a resin composition that is excellent in dispersibility and that satisfies the physical requirements (moldability, impact resistance, heat resistance) of containers and the like that use the resin composition. In particular, it has been found that the resin composition of the present disclosure has significantly improved impact resistance at low temperatures. Whether the molecular weight distribution of the resin component is controlled can be determined by the peak top position of the resin component (logM top) and whether the half-width falls within a specific range.
[0017] The resin composition according to the present disclosure, and a resin layer, a laminate, a container, and an article using the same will be described below, but the present invention is not limited to the following examples.
[0018] In the present disclosure, the thickness direction 1 refers to the thickness direction of the resin layer (laminate) as shown in Fig. 1, and the width direction 2 refers to a direction different from the thickness direction 1 and perpendicular to the longitudinal direction 3 of the resin layer (laminate). For example, when the resin layer (laminate) is manufactured by a melt extrusion molding method, the longitudinal direction 3 corresponds to the machine direction (MD), and the width direction 2 corresponds to the transverse direction (TD) perpendicular to the MD.
[0019] Hereinafter, an embodiment of the present disclosure (hereinafter, may be referred to as "the present embodiment") will be described. In this disclosure, numerical values related to "greater than or equal to," "less than or equal to," "to" and the like in describing a numerical range are numerical values that can be arbitrarily combined.
[0020] Furthermore, provisions that are considered to be preferred may be adopted arbitrarily. That is, one provision that is considered to be preferred may be adopted in combination with one or more other provisions that are considered to be preferred. A combination of preferred provisions may be considered to be more preferred.
[0021] [Resin composition] The resin composition of the present embodiment is required to be a resin composition that contains one or more resin components and one or more inorganic particles, and in a differential molecular weight distribution curve of the resin components by resin permeation chromatography (GPC), the half-value width of a peak having a peak top between 4.5 and 6.5 is 0.90 or more and 2.00 or less.
[0022] Hereinafter, in this disclosure, the term "differential molecular weight distribution curve" refers to a curve plotting the concentration fraction (W) differentiated by the logarithm of the molecular weight M, relative to logM determined from the molecular weight M calibrated with monodisperse polystyrene (PS) in GPC measurement. Log refers to common logarithm with a base of 10. For details, see the explanation, examples, and FIG. 4 described later.
[0023] The inorganic particles are poorly soluble in the resin component and may be partially dissolved, but it is preferable that the resin composition is in a state in which the inorganic particles are dispersed in the resin composition.
[0024] The resin composition of the present embodiment may be used to form a resin layer, which will be described later, as shown in Fig. 2, or may be used as a so-called master batch. When used as a master batch, a resin component or the like may be further added and used as a resin composition for forming a resin layer, as shown in Fig. 3. Hereinafter, unless otherwise specified, the resin composition means a resin composition used to form a resin layer, and when referring to a master batch, it is described as a master batch.
[0025] The master batch means a product in process that is diluted 2 to 10 times with a resin component to obtain a resin composition for forming a resin layer. The use of a master batch is preferable because the content of inorganic particles in the resin composition can be easily adjusted by dilution.
[0026] In the present disclosure, for example, "diluting by two times" means that 1 mass gram of a resin component is added to 1 mass gram of a master batch, and stirred as necessary to obtain a resin composition.
[0027] The resin composition of the present embodiment can be preferably used as a container for contents described below, since the resin layer using the resin composition has excellent impact resistance. For example, the contents can be liquid or solid foods such as food, beverages, cooking oils, and seasonings, precision instruments, stationery, industrial products such as screws and nuts, and daily consumables such as detergents and shampoos. Since the resin composition has excellent impact resistance especially at low temperatures, it is excellent for containers used at low temperatures, such as for frozen foods.
[0028] In addition, because it has excellent moldability, it is excellent as a container that requires dimensional stability for precision instruments, etc. Furthermore, because it has excellent impact resistance even at high temperatures, it can withstand heating in a microwave oven, etc., and has excellent properties as a container expected to be used over a wide temperature range.
[0029] In addition, the resin composition of the present embodiment has excellent dispersibility of inorganic particles in the resin component, so that the content of inorganic particles can be increased. Furthermore, since the inorganic particles are unlikely to precipitate from the resin composition, the resin composition has long-term storage stability, and is easy to manufacture, so that the productivity is also excellent, which is preferable.
[0030] The resin composition of the present embodiment may contain the resin component and inorganic particles in the above-mentioned amounts, but may further contain additives that are usually contained in resin compositions in the field, with the additives described below being preferred.
[0031] The resin component, inorganic particles and additives will be described below, but are not limited to the following examples.
[0032] <Resin component> The resin component must have a half-width of a peak having a peak top at 4.5 to 6.5 in a differential molecular weight distribution curve by resin permeation chromatography (GPC) of 0.90 to 2.00.
[0033] The resin component preferably contains a thermoplastic resin or a thermosetting resin, and in order to facilitate the production of the container described below, it preferably contains one or more types of thermoplastic resin.
[0034] The total content of the resin components in the resin composition of the present embodiment is preferably 20.0% by mass or more and 70.0% by mass or less. The measurement method by GPC, the method of identifying the peaks, and the half width of the peaks will be described later.
[0035] In order to have a peak top in the specific region, it can be achieved by appropriately adjusting the contents of the multiple components (hereinafter referred to as polymers for the sake of explanation) that make up the resin component. The polymer itself has a molecular weight distribution, but since the molecular weight distribution is approximately additive, when multiple polymers are used, if the molecular weight distribution of each polymer is known, the content of each polymer can be appropriately determined to easily adjust the position of the peak top. Similarly, for the half-width of the peak, if the molecular weight distribution of each polymer is known, the content of each polymer can be adjusted by simulation using a spreadsheet application or the like to obtain the desired half-width. When the polymer is obtained by polymerizing a specific monomer, if the differential molecular weight distribution curve of this polymer has the required peak top and half-width, this may be used as is. However, it is generally difficult to set the differential molecular weight distribution curve of the polymer to the required range, although it can be done by selecting polymerization conditions such as temperature conditions, selection of catalyst type, catalyst amount, solvent selection, and solvent amount. In addition, even if the polymerization conditions can be determined, it is extremely difficult to scale up the polymerization to an industrial scale and further maintain the conditions during the polymerization reaction. For this reason, in terms of production efficiency, it is preferable to prepare a plurality of polymers having different differential molecular weight distribution curves and mix them appropriately so as to have a peak top and half width at the desired positions.
[0036] The peak top 6 means the highest point in the range of 4.5 to 6.5 in logM, which is the horizontal axis of the differential molecular weight distribution curve, and the logM topFrom the above, the molecular weight M of the top 6 peak top can be calculated.
[0037] The logM top is preferably in the range of 4.7 to 6.2, more preferably in the range of 4.8 to 6.0, even more preferably in the range of 5.0 to 5.7, and even more preferably in the range of 5.1 to 5.6. When two or more peak tops are present in the above range, the highest peak is regarded as the peak top.
[0038] In order to simultaneously satisfy at least two of the following: to improve impact resistance, to improve moldability, to improve long-term storage stability, to provide an environmentally friendly product by increasing the total content of the inorganic particles and reducing the amount of resin used, and to improve heat resistance, the half-width of the peak is preferably 0.95 to 1.90, more preferably 0.97 to 1.80, even more preferably 0.98 to 1.70, and even more preferably 0.99 to 1.60.
[0039] The half-width 9 of the peak of the resin component means the half-width of the peak to which the peak top 6 belongs. When multiple peaks exist and the peaks cannot be separated, the half-width means the half-width of the peak including the multiple peaks that cannot be separated. FIG. 4 shows an example of multiple peaks that cannot be separated. For example, in the differential molecular weight distribution curve obtained as described below, when the range of logM between 2.0 and 8.0 is 9.0 cm, the dW / dlogM of the peak top 6 is the peak top height 8, and the width of 50% of this peak top height (the width is the absolute value of the difference between logM1 and logM2 at two points where a straight line parallel to the horizontal axis at 50% of the peak top height intersects with the curve to which the peak top 6 belongs in the differential molecular weight distribution curve) is the half-width 9.
[0040] The resin component is dissolved in tetrahydrofuran (THF) and a differential molecular weight distribution curve 5 is obtained by a resin permeation chromatography (GPC) method. The M means a molecular weight calculated as styrene using standard polystyrene (monodisperse).
[0041] From this differential molecular weight distribution curve 5, logM top and M top The peak top can be calculated by logM top means.
[0042] The GPC measurement is preferably carried out, for example, as follows. Equipment: Size exclusion chromatography equipment (Tosoh HLC-8320GPC) Column temperature: 40℃ Detection method: Refractive index detector (RID) Mobile phase: Tetrahydrofuran (THF, stabilizer free) Sample concentration: 2% by mass Column: TSKgel SuperHM-M (2 columns in series) Calibration curve: Created using standard polystyrene (monodisperse)
[0043] In the resin composition of this embodiment, the lower limit of the total content of the resin components is more preferably 22.0% by mass or more, even more preferably 25.0% by mass or more, even more preferably 28.0% by mass or more, even more preferably 30.0% by mass or more, and even more preferably 35.0% by mass or more. In order to simultaneously satisfy at least two of the following: to improve impact resistance, to improve moldability, and to improve long-term storage stability, the upper limit is more preferably 68.0% by mass or less, even more preferably 65.0% by mass or less, even more preferably 62.0% by mass or less, and even more preferably 60.0% by mass or less, and even more preferably 60.0% by mass or less.
[0044] When used as the master batch, the upper limit of the total content of the resin components in the resin composition of this embodiment is preferably 30.0 mass% or less, more preferably 28.0 mass% or less, even more preferably 25.0 mass% or less, and even more preferably 24.0 mass% or less, and the lower limit is preferably 20.0 mass% or more, more preferably 21.0 mass% or more, even more preferably 22.0 mass% or more, and even more preferably 23.0 mass% or more.
[0045] The value obtained by dividing the total content of the resin components by the total content of the inorganic particles (total content of the resin components (g by mass) / total content of the inorganic particles (g by mass)) is preferably 0.4 or more and 2.0 or less, more preferably 0.6 or more and 1.6 or less, even more preferably 0.7 or more and 1.4 or less, and even more preferably 0.8 or more and 1.2 or less, in order to improve the balance between at least two of impact resistance, moldability, heat resistance, elution of components derived from the inorganic particles, and long-term storage stability.
[0046] <<Thermoplastic resin>> The resin component preferably contains one or more thermoplastic resins.
[0047] The total content of the thermoplastic resin in the resin composition of this embodiment is preferably 20.0% by mass or more and 70.0% by mass or less, and the lower limit of the total content of the thermoplastic resin is more preferably 22.0% by mass or more, even more preferably 25.0% by mass or more, even more preferably 28.0% by mass or more, more preferably 30.0% by mass or more, and even more preferably 35.0% by mass or more, in order to improve impact resistance, improve moldability, and improve long-term storage stability, and the upper limit is 68.0% by mass or less, more preferably 65.0% by mass or less, even more preferably 62.0% by mass or less, more preferably 60.0% by mass or less, and even more preferably 60.0% by mass or less.
[0048] When used as the master batch, the upper limit of the total content of the thermoplastic resins in the resin composition of this embodiment is preferably 30.0 mass% or less, more preferably 28.0 mass% or less, even more preferably 25.0 mass% or less, and even more preferably 24.0 mass% or less, and the lower limit is preferably 20.0 mass% or more, more preferably 21.0 mass% or more, even more preferably 22.0 mass% or more, and even more preferably 23.0 mass% or more.
[0049] Examples of the thermoplastic resin include polyolefin resins, polyester resins, and polystyrene resins, with polyolefin resins being preferred due to their excellent moldability.
[0050] In order to improve impact resistance, the mass average molecular weight (Mw) of the polyolefin resin is preferably 30,000 or more and 1,000,000 or less, more preferably 50,000 or more and 800,000 or less, even more preferably 70,000 or more and 700,000 or less, and even more preferably 90,000 or more and 600,000 or less.
[0051] In order to improve impact resistance, the polydispersity (Mw / Mn) of the polyolefin resin is preferably 1.5 or more and 9.0 or less, more preferably 2.0 or more and 8.0 or less, even more preferably 2.5 or more and 7.5 or less, and even more preferably 3.0 or more and 7.0 or less.
[0052] In order to improve impact resistance, the glass transition point (Tg) of the polyolefin resin is preferably 100°C or higher, more preferably 108°C or higher, even more preferably 115°C or higher, and even more preferably 117°C or higher.
[0053] The upper limit of Tg is not particularly limited, but from the viewpoint of moldability, it is preferably 150°C or less, more preferably 140°C or less, even more preferably 130°C or less, and even more preferably 125°C or less.
[0054] In order to achieve the above Tg range, it is preferable to add a metallocene-based polyolefin-based resin to the polyolefin-based resin.
[0055] When a polyolefin resin is used as the thermoplastic resin, the total content of the polyolefin resin relative to the total content of the resin composition is preferably 20.0% by mass or more and 70.0% by mass or less. The lower limit of the total content of the thermoplastic resin is more preferably 22.0% by mass or more, even more preferably 25.0% by mass or more, even more preferably 28.0% by mass or more, more preferably 30.0% by mass or more, and even more preferably 35.0% by mass or more, in order to improve impact resistance, improve moldability, and improve long-term storage stability. The upper limit is more preferably 68.0% by mass or less, even more preferably 65.0% by mass or less, even more preferably 62.0% by mass or less, and even more preferably 60.0% by mass or less, in order to increase the total content of the inorganic particles and reduce the amount of resin used, and to improve heat resistance, and is more preferably 60.0% by mass or less, and even more preferably 60.0% by mass or less.
[0056] When used as the master batch, the upper limit of the total content of the polyolefin resins in the resin composition of this embodiment is preferably 30.0 mass% or less, more preferably 28.0 mass% or less, even more preferably 25.0 mass% or less, and even more preferably 24.0 mass% or less, and the lower limit is preferably 20.0 mass% or more, more preferably 21.0 mass% or more, even more preferably 22.0 mass% or more, and even more preferably 23.0 mass% or more.
[0057] As the polyolefin-based resin, a polyolefin-based resin containing as the main component a component unit derived from an olefin is preferred, and the component unit derived from an olefin is preferably contained in the polyolefin-based resin at 60.0 mass% or more, more preferably 70.0 mass% or more, even more preferably 80.0 mass% or more, even more preferably 90.0 mass% or more, and extremely preferably 95.0 mass% or more.
[0058] The polyolefin resin of the present disclosure may be one obtained by a general production method, but methods using a metallocene catalyst, a Ziegler-Natta catalyst, a radical initiator, etc. are preferred. When impact resistance at low temperatures is required, metallocene polyolefin resins produced using a metallocene catalyst are preferred, as they have a narrow molecular weight distribution and high copolymerizability. Examples of polyolefin resins include polypropylene resins (hereinafter referred to as PP resins) and polyethylene resins (hereinafter referred to as PE resins).
[0059] It is also preferable to use a metallocene-based polyolefin resin in combination with a polyethylene resin produced without using a metallocene-based catalyst, and a combination of a metallocene-based PP resin and a PP resin, a combination of a metallocene-based PE resin and a PE resin, and further combinations thereof are also preferred.
[0060] The combined use of a metallocene-based polyolefin resin and a polyethylene resin produced without using a metallocene-based catalyst is preferred because it makes it easier to adjust the peak molecular weight and half-width according to requirements.
[0061] (Polypropylene resin (PP resin)) The polypropylene-based resin (PP resin) in this embodiment may be a polypropylene homopolymer, or may be a copolymer of propylene and another α-olefin.
[0062] The polypropylene homopolymer may be an isotactic type in which the chirality of carbon atoms to which methyl groups are added is in the same direction relative to the polymer main chain, a syndiotactic type in which the carbon atoms are arranged alternately, an atactic type in which the carbon atoms are arranged randomly, or a hemiisotactic type which is a combination of these.
[0063] The copolymer preferably contains 60.0% by mass or more of component units derived from propylene in the PP resin, more preferably 70.0% by mass or more, even more preferably 80.0% by mass or more, and even more preferably 85.0% by mass or more.
[0064] The copolymer may be any one of a polypropylene random copolymer (random copolymer), a polypropylene block copolymer (block copolymer), a binary copolymer, a ternary copolymer, etc., and preferred examples thereof include an ethylene-propylene random copolymer, a butene-1-propylene random copolymer, an ethylene-butene-1-propylene random terpolymer, and an ethylene-propylene block copolymer.
[0065] Preferred examples of the α-olefin include α-olefins having 4 to 10 carbon atoms (such as ethylene, 1-butene, isobutylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3,4-dimethyl-1-butene, 1-heptene, and 3-methyl-1-hexene).
[0066] (Polyethylene resin (PE resin)) The polyethylene resin (PE resin) in the present disclosure may be a polyethylene homopolymer, but may also be a copolymer of ethylene and another α-olefin.
[0067] The copolymer preferably contains component units derived from ethylene in a proportion of 70.0% by mass or more in the PE resin, more preferably 80.0% by mass or more, even more preferably 90.0% by mass or more, and even more preferably 95.0% by mass or more.
[0068] Preferred examples of polyethylene resins include low-density polyethylene (LDPE), high-density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMW-PE), ethylene-vinyl acetate copolymer, ethylene-propylene copolymer, ethylene-propylene-butene 1 copolymer, ethylene-buten-1-yl copolymer, ethylene-hexen-1-yl copolymer, ethylene-4-methylpenten-1-yl copolymer, and ethylene-octen-1-yl copolymer.
[0069] <Inorganic particles> The inorganic particles used in the present embodiment are particles classified as inorganic substances, and their median diameter (D 50 ) is preferably 1 μm or more and 100 μm or less. 50 means a value determined by a laser diffraction / scattering method, and can be measured, for example, by the method described in the Examples. The shape of the particle is preferably powder, spheres, flakes, granules, or fibers.
[0070] Examples of the inorganic particles include the following: carbonates, sulfates, silicates, phosphates, or borates of metals (calcium, magnesium, aluminum, titanium, iron, zinc, etc.); oxides of metals (calcium, magnesium, aluminum, titanium, iron, zinc, etc.); hydrates of the above salts or oxides, which may be synthetic or derived from natural minerals.
[0071] More specifically, calcium carbonate, magnesium carbonate, zinc oxide, titanium oxide, silica, alumina, clay, talc, kaolin, aluminum hydroxide, magnesium hydroxide, aluminum silicate, magnesium silicate, calcium silicate, aluminum sulfate, magnesium sulfate, calcium sulfate, magnesium phosphate, barium sulfate, silica, carbon black, zeolite, molybdenum, diatomaceous earth, and bentonite are preferred, calcium carbonate, magnesium carbonate, zinc oxide, titanium oxide, silica, alumina, talc, carbon black, zeolite, molybdenum, diatomaceous earth, and bentonite are more preferred, calcium carbonate, silica, alumina, and talc are even more preferred, and calcium carbonate is even more preferred.
[0072] The talc is classified as a clay mineral and is a silicate mineral (Mg3Si4O 10 It is a type of phyllosilicate mineral, composed of magnesium hydroxide and silicate, and includes rocks that are primarily composed of this mineral. It is also called talc, steatite, soapstone, French chalk, and lava.
[0073] The inorganic component is preferably a mixture of salt particles such as carbonates, sulfates, silicates, phosphates, or borates of the metals, and neutral particles such as metal oxides, silica, carbon black, zeolites, diatomaceous earth, and natural products such as bentonite. When salt particles alone are used, the container using them has basic properties, so it is preferable to use them together with neutral particles. In particular, when the contents are susceptible to the basicity of food, etc., the contents are altered, so when basic particles are used, it is more preferable to use them in combination with neutral particles. By combining them in this way, it is possible to increase the content of inorganic particles while suppressing basicity, so that the content of the resin composition in the resin composition can be reduced, which is preferable.
[0074] The inorganic particles may be used alone or in combination of two or more kinds. When two or more kinds are used in combination, preferred combinations include a combination containing talc and calcium carbonate, a combination containing talc and magnesium carbonate, a combination containing talc and titanium oxide, a combination containing talc and carbon black, a combination containing talc and silica, a combination containing talc and diatomaceous earth, a combination containing talc and bentonite, a combination containing calcium carbonate and carbon black, a combination containing calcium carbonate and silica, a combination containing calcium carbonate and diatomaceous earth, and a combination containing calcium carbonate and bentonite, and more preferred are a combination containing talc and calcium carbonate, a combination containing talc and magnesium carbonate, a combination containing talc and silica, a combination containing calcium carbonate and carbon black, a combination containing calcium carbonate and silica, a combination containing calcium carbonate and diatomaceous earth, and a combination containing calcium carbonate and bentonite, and more preferred are a combination containing talc and calcium carbonate, and even more preferred are a combination containing talc and calcium carbonate, and even more preferred are a combination containing talc and calcium carbonate. The inorganic particles may be surface-modified or coated to improve dispersibility. The coating may be a coating with an organic substance such as silicone, or a coating with an inorganic substance such as silica gel or alumina.
[0075] The total content of the inorganic particles in the resin composition of the present embodiment is preferably 10.0% by mass or more and 80.0% by mass or less.
[0076] The lower limit of the total content of the inorganic particles is more preferably 30.0% by mass or more, even more preferably 35.0% by mass or more, even more preferably 40.0% by mass or more, excellently preferably 42.0% by mass or more, more excellently preferably 45.0% by mass or more, and even more excellently preferably 48.0% by mass or more; the upper limit is more preferably 68.0% by mass or less, even more preferably 65.0% by mass or less, even more preferably 62.0% by mass or less, and excellently preferably 60.0% by mass or less, in order to increase the total content of the inorganic particles, to provide an environmentally friendly product with a reduced amount of resin used, and to improve heat resistance.
[0077] In the present disclosure, the "long-term storage stability" is determined by visually observing the precipitation of solid matter (inorganic particles) from the resin composition when the resin composition is left to stand at 25°C for 30 days, and when no solid matter is observed, the resin composition is determined to have excellent long-term storage stability.
[0078] When used as the master batch, the upper limit of the total content of the inorganic particles is preferably 90.0 mass% or less, more preferably 86.0 mass% or less, even more preferably 84.0 mass% or less, and even more preferably 82.0 mass% or less, and the lower limit is preferably 70.0 mass% or more, more preferably 73.0 mass% or more, even more preferably 75.0 mass% or more, and even more preferably 78.0 mass% or more.
[0079] When calcium carbonate is used as the inorganic particles, the D 50 is preferably 1.0 μm or more and 15.0 μm or less, more preferably 2.0 μm or more and 10.0 μm or less, and even more preferably 3.0 μm or more and 8.0 μm or less.
[0080] When talc is used as the inorganic particles, its D 50 is preferably 3.0 μm or more and 20.0 μm or less, more preferably 4.0 μm or more and 18.0 μm or less, and even more preferably 5.0 μm or more and 16.0 μm or less.
[0081] <Additives> If necessary, the resin composition may further contain additives, such as foaming agents, colorants, lubricants, antistatic agents, antioxidants, ultraviolet absorbers, and light stabilizers that are commonly used in the art.
[0082] For example, as the ultraviolet absorbing agent, a benzotriazole-based compound is preferable.
[0083] Since these additives improve impact resistance and moldability, the total content of the additives relative to the total content of the resin composition is preferably 10.0 mass% or less, more preferably 8.0 mass% or less, even more preferably 5.0 mass% or less, even more preferably 3.0 mass% or less, and even more preferably 1.0 mass% or less.
[0084] There is no particular restriction on the lower limit as long as the resin composition of the present embodiment exhibits the effects of the invention.
[0085] [Resin Layer] The resin layer of the present embodiment is required to be a resin layer using the above-mentioned resin composition.
[0086] In this embodiment, the thickness of the resin layer is preferably 50 μm or more, more preferably 100 μm or more, even more preferably 150 μm or more, and even more preferably 200 μm or more in order to improve impact resistance, and is preferably 2000 μm or less, more preferably 1800 μm or less, even more preferably 1500 μm or less, even more preferably 1200 μm or less, and even more preferably 1000 μm or less in order to improve moldability.
[0087] [Laminate] The laminate of this embodiment is required to include the resin layer and one or two surface layers.
[0088] The laminate of the present embodiment preferably includes the resin layer and further includes a surface layer on one or both sides of the resin layer. The surface layer may be formed directly on the resin layer, but if necessary, the surface layer may be laminated via a primer layer or an adhesive layer as another layer.
[0089] In particular, when a basic compound such as calcium carbonate is used as the inorganic particles and the contents are affected by the basicity, it is preferable to provide a surface layer on the content side of the resin layer, since the effect of the basic compound on the contents can be suppressed. It is preferable to provide a surface layer on the content side of the resin layer, since the content of the resin composition of the basic compound such as calcium carbonate can be increased.
[0090] The layer thickness of the laminate is determined by the configuration of the resin layer, surface layer and other layers, and the layer thickness of each layer, but in order to improve moldability and impact resistance, it is preferably 50 μm or more and 2000 μm or less, more preferably 100 μm or more and 1800 μm or less, even more preferably 150 μm or more and 1500 μm or less, even more preferably 180 μm or more and 1200 μm or less, and even more preferably 200 μm or more and 1000 μm or less.
[0091] <<Surface layer>> In order to suppress the influence of the base in the contents and to improve moldability, the thickness of the surface layer is preferably 1 μm or more and 500 μm or less, more preferably 2 μm or more and 300 μm or less, even more preferably 5 μm or more and 200 μm or less, even more preferably 0 μm or more and 100 μm or less, and even more preferably 10 μm or more and 80 μm or less.
[0092] The surface layer is preferably the thermoplastic resin layer, and more preferably the PP resin layer substantially free of inorganic particles.
[0093] 〔container〕 The container of this embodiment is required to include the resin layer or the laminate. The container is excellent in impact resistance, heat resistance, and chemical stability, and therefore is excellent as a container for protecting the contents described below during transportation. In addition, since the container has excellent moldability, it can be manufactured at low cost, and since it can be molded to fit the shape of a precision instrument when transporting the precision instrument, it is excellent as a container because it can suppress the precision instrument from moving and being damaged during transportation. The container shape may be appropriately determined based on the shape of the contents, etc.
[0094] [Goods] The article of this embodiment is required to include the container and the contents described below.
[0095] <<Contents>> The contents may be liquids, liquid crystals, or solids, such as food, beverages, cooking oils, seasonings, precision instruments such as CPUs and memory, stationery, industrial products such as screws or nuts, machine tools such as pliers or hammers, and daily consumables such as detergents or shampoos.
[0096] [Methods for producing resin composition, resin layer, and laminate] Examples of the methods for producing the resin composition, resin layer, laminate, and container of the present embodiment will be described below, but the methods are not limited thereto.
[0097] The resin composition of the present embodiment can be produced, for example, by the following production method.
[0098] Two or more types of inorganic particles and one or more types of resin components and, if necessary, additives in appropriate amounts are melt-mixed and cooled to form a master batch.
[0099] A two-kind three-layer co-extruder can be used to manufacture a laminate. More specifically, as a resin composition for forming the resin layer 110 shown in FIG. 5, an appropriate blending amount of the master batch, one or more resin components, and additives as necessary are melt-mixed and fed to a single extruder, and raw materials for forming the surface layer 121 and the surface layer 122 on both sides are also fed to the extruder, and fed to a two-kind three-layer feed block type T die at a predetermined temperature. A three-layer sheet is extruded through a die adjusted to an appropriate lip clearance, rolled with three polishing rolls, cooled to room temperature, and a three-layer sheet including the resin layer 110 having the surface layer 121 and the surface layer 122 laminated on both sides is formed, and then wound into a roll, and the laminate can be manufactured.
[0100] When forming a laminate without going through a masterbatch, a resin composition for forming a resin layer can be used in an extruder in appropriate amounts of two or more types of inorganic particles, one or more resin components, and additives as necessary. Although an example having two surface layers has been described in the above-mentioned manufacturing method, by not forming unnecessary surface layers, it is possible to manufacture a laminate having a desired resin layer or a surface layer on only one side.
[0101] Although the coextrusion method has been described as a method for producing a laminate, a T-die method, an inflation method, a calendar method, etc. can also be used.
[0102] [Method of manufacturing container] The laminate (resin composition) exemplified above can be molded into a desired shape by a method commonly used in the art, such as vacuum molding, pressure molding, match mold molding, etc.
[0103] The resin composition, resin layer, laminate, container, and article of the present embodiment preferably satisfy the following items [1] to
[13] . [1] A resin composition comprising one or more resin components and one or more inorganic particles, wherein in a differential molecular weight distribution curve of the resin components as measured by gel permeation chromatography (GPC), the half-width of a peak having a peak top between 4.5 and 6.5 is 0.90 or more and 2.00 or less. [2] The resin composition according to [1], containing one or more thermoplastic resins as the resin component. [3] The resin composition according to [2], wherein the thermoplastic resin is a polyolefin resin. [4] The resin composition according to any one of [1] to [3], wherein the polydispersity (Mw / Mn) of the resin component is 1.5 or more and 9.0 or less. [5] The resin composition according to any one of [1] to [4], wherein the inorganic particles contain calcium carbonate. [6] The median diameter (D 50 The resin composition according to any one of [1] to [5], wherein the average particle size of each of the particles is 1 μm or more and 100 μm or less. [7] The resin composition according to any one of [1] to [6], wherein a value obtained by dividing the total content of the resin components by the total content of the inorganic particles (total content of the resin components (g by mass) / total content of the inorganic particles (g by mass)) is 0.4 or more and 2.0 or less. [8] The resin composition according to any one of [1] to [7], further comprising an additive. [9] A resin layer using the resin composition according to any one of [1] to [8].
[10] A laminate comprising the resin layer according to [9] and one or two surface layers.
[11] A container comprising the resin layer described in [9].
[12] A container comprising the laminate described in
[10] .
[13] An article comprising the container and contents described in
[11] or
[12] . EXAMPLES
[0104] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples in any way.
[0105] (Evaluation method) 1. Dispersibility The state of melt mixing in a single extruder described below was visually observed and rated on the following three levels, with A and B being considered acceptable. Grade A (marked as A in the table): Uniformly dispersed. Grade B (marked as B in the table): Some solid matter was not dispersed in the resin, but the moldability evaluation below gave it a grade of A or B, and it poses no practical problems. C rating (listed as C in the table): The material cannot be dissolved and mixed, or the moldability rating below is C.
[0106] 2.Moldability The containers formed from the laminate were visually inspected and rated on the following three levels, with A and B being considered acceptable. Grade A (marked as A in the table): No defects (holes, uneven thickness or burrs) were found in the container. B rating (marked as B in the table): Test containers were found to have whitening only around the protruding parts of the mold used during molding, but there were no problems with the manufacturing process. C rating (marked as C in the table): Defects were found on the entire bottom surface of the container.
[0107] 3. Shock resistance The resulting container was left to stand for 1 hour in a thermostatic chamber at 60°C, 25°C or -20°C. While maintaining each of the above temperatures, a 300g stainless steel chisel (with a hemispherical tip with a radius of 6.35mm) was dropped vertically onto the bottom of the container from a height of 100cm. After the drop, the bottom of the container was visually inspected and rated on the following three levels. A rating of A was considered a pass. Rating A (listed as A in the table): A scratch was visible where the object fell, but the container was not penetrated. Rating B (marked as B in the table): A hole was found through the container at the point of impact, but no other damage was found on the bottom of the container. C rating (marked as C in the table): Damage spreads across the entire bottom of the container.
[0108] 4.Heat resistance The container was left to stand at 120°C for 8 hours, and the appearance and surface condition were visually inspected. If there was no change, it was rated as having heat resistance (indicated as A in the table; the evaluation was deemed to be pass). If there was a change in appearance, it was rated as not having heat resistance (indicated as B in the table; the evaluation was deemed to be fail).
[0109] 5.Layer thickness The thickness of each layer was determined by the following method. The sample was cut in the thickness direction using a microtome (REM-710 ritratome, manufactured by Yamato Koki Kogyo Co., Ltd.), and the cross section obtained was observed with a laser microscope (VHX-6000, manufactured by Keyence Co., Ltd.) to determine the layer thickness.
[0110] 6. Average particle size (D 50 ) Average particle size at 50% cumulative volume (D 50 The particle size distribution was measured using a laser diffraction / scattering type particle size distribution analyzer (Partica LA-950 manufactured by Horiba, Ltd.) by adding the powder to be measured to the flow cell of the device and subjecting it to ultrasonic treatment. Using the cumulative curve of the particle size distribution obtained, the particle size at which the particle size reaches 50% (volume basis) of the total particle size by sequentially accumulating the particle size distribution from the smallest particle size was determined as the average particle size (D 50 ) was decided.
[0111] 7.Molecular weight etc. The peak top, half width, number average molecular weight (Mn), weight average molecular weight (Mw), average molecular weight (Mz) and polydispersity (Mw / Mn) of the resin components used in each of the Examples and Comparative Examples were determined as follows.
[0112] Tetrahydrofuran (THF) was added to the resin component to be measured, and the mixture was stirred to prepare a homogeneous solution of 2 mg / mL. The resulting solution was filtered through a membrane filter (PTFE, pore size: 0.45 μm), and the filtrate was subjected to molecular weight measurement as follows. When inorganic particles were contained, the inorganic particles were removed. Equipment: Size exclusion chromatography equipment (Tosoh HLC-8320GPC) Eluent: Tetrahydrofuran (without stabilizer) Column: TSKgel SuperHM-M (2 columns in series) Detector: Differential refractometer Measurement temperature: 40℃ Flow rate: 0.6mL / min Injection volume: 20μL Molecular weight calculation conditions Relative molecular weight values were calculated based on standard substances. Standard material: 12 standard polystyrenes (molecular weight 504 to 1.09 x 10 6 ) Calibration curve: Cubic approximation curve
[0113] From the obtained results, a differential molecular weight distribution curve was created (Figure 4), with logM calculated from the molecular weight M calibrated with monodisperse polystyrene (PS) on the horizontal axis and the value (dW / dlogM) obtained by differentiating the concentration fraction (W) with the logarithm of the molecular weight M on the vertical axis. From the obtained differential molecular weight distribution curve, a peak top (logM top ) for the peak having the peak top 6, a straight line parallel to the horizontal axis is drawn at 50% of the height 8 of the peak top 6, and the absolute value of the difference between logM1 and logM2 at the two points where this straight line intersects with the curve to which the peak top 6 belongs in the differential molecular weight distribution curve is taken as the half-width 9. top to the molecular weight M top It was decided.
[0114] 8.Materials used (Resin component) Polypropylene resin (PP resin): A suitable combination of polypropylene block copolymers was used. The logM of each resin component top The half-width, Mw and Mw / Mn are shown in the table below. In Table 1, "-" indicates not measured.
[0115] [Table 1]
[0116] Example 1 49 parts by mass of resin component 1 and inorganic particles (calcium carbonate: manufactured by Shiraishi Calcium Co., Ltd., product name: Whiten SB Aka, D 50 51 parts by mass of PP resin (=4.3 μm) was supplied to a single extruder (diameter 65 mm, L / D: 32), and the PP resin was also supplied to a single extruder (diameter 130 mm, L / D: 32) as a raw material for the surface layers 121 and 122. The raw materials melted and mixed at a predetermined temperature from each extruder were supplied to a two-kind three-layer feed block type T-die. A three-layer sheet was extruded from a die adjusted to an appropriate lip clearance. The sheet was rolled with three polishing rolls, cooled to room temperature, and molded into a three-layer sheet with a total thickness of 500 μm, and then wound into a roll to form the laminate 100. The surface layer 121 had a thickness of 100 μm, the surface layer 122 had a thickness of 100 μm, and the resin layer 110 had a thickness of 300 μm.
[0117] The laminate produced as described above was deep-drawn to produce a container. The laminate 100 was molded into a cup-shaped test container with an opening diameter of 50 mm, a bottom diameter of 45 mm, and a height of 55 mm, using a single-shot molding machine (manufactured by NK Enterprises).
[0118] The results of dispersibility, moldability, impact resistance and heat resistance are shown in Table 2. (Examples 2 and 3) The laminate and test container of Example 2 were produced in the same manner as in Example 1, except that resin component 1 was replaced with resin component 2, and the laminate and test container of Example 3 were produced in the same manner as in Example 1, except that resin component 1 was replaced with resin component 3.
[0119] The results of dispersibility, moldability, impact resistance and heat resistance are shown in Table 2. (Comparative Examples 1 and 2) A laminate and a test container were produced in the same manner as in Example 1, except that resin component 1 was replaced with resin component 4 (Comparative Example 1) and resin component 1 was replaced with resin component 5 (Comparative Example 2).
[0120] The results of dispersibility, moldability, impact resistance and heat resistance are shown in Table 2. In Table 2, "-" indicates that the laminate could not be produced and therefore could not be evaluated.
[0121] [Table 2]
[0122] It was confirmed that the resin compositions of Examples 1, 2, and 3 were practically problem-free. In contrast, the resin composition of Comparative Example 1 using Resin Component 4 had low dispersibility of inorganic particles, and the moldability, impact resistance, and heat resistance of the test container were low. The resin composition of Comparative Example 2 using Resin Component 5 had even lower dispersibility than Comparative Example 1, and it was not possible to prepare a laminate using this composition, and it was not possible to evaluate the moldability, impact resistance, and heat resistance. [Industrial Applicability]
[0123] The resin composition, resin layer, laminate, container, and article of this embodiment use a resin component with a controlled molecular weight distribution, which provides excellent dispersibility of inorganic particles, and containers and the like using such resin components satisfy physical requirements (moldability, impact resistance, heat resistance), and therefore the containers of this embodiment are suitable for use with food, etc. [Explanation of symbols]
[0124] 1 Thickness direction 2 Width direction 3 Longitudinal direction 5 Differential molecular weight distribution curve 6. Peak Top 7 logM at peak top top 8 Peak top height 9 Peak half-width 10 logM1 at molecular weight M1 11 logM2 when molecular weight M2 100 Laminate 110 Resin layer 120 Surface layer 121 Surface layer 122 Surface layer
Claims
1. One or more resin components; A resin composition containing one or more types of inorganic particles, The total content of the resin components in the resin composition is 20.0% by mass or more, The resin component contains one or more thermoplastic resins, the thermoplastic resin contains a polyolefin resin, and in a differential molecular weight distribution curve by gel permeation chromatography (GPC), the half-width of a peak having a peak top in the range of 4.5 to 6.5 is 0.90 to 2.00, and the half-width is logM 1 and logM 2 is the absolute value of the difference between the logM 1 and the logM 2 are two points at which a straight line parallel to the horizontal axis at 50% of the height of the peak top intersects with a curve to which the peak top belongs in the differential molecular weight distribution curve, the dW / dlogM of the peak top being the height of the peak top in the differential molecular weight distribution curve, The inorganic particles contain calcium carbonate, The content of the calcium carbonate in the resin composition is 45.0% by mass or more, and The volume average particle diameter (D 50 ) is 1 μm or more and 100 μm or less, A resin composition excluding a resin composition in which cellulose fibers and aluminum are dispersed in the resin component.
2. The resin composition according to claim 1 , wherein the polyolefin resin contains a polypropylene resin, and the content of the polypropylene resin is 35.0 mass % or more based on the total of the resin composition.
3. The resin composition according to claim 1, wherein the polydispersity (Mw / Mn) of the resin component is 1.5 or more and 9.0 or less.
4. 2. The resin composition according to claim 1, wherein a value obtained by dividing the total content of the resin components by the total content of the inorganic particles (total content of the resin components (mass g) / total content of the inorganic particles (mass g)) is 0.4 or more and 2.0 or less.
5. The resin composition according to claim 1 , further comprising an additive.
6. A resin layer using the resin composition according to claim 1.
7. A laminate comprising the resin layer according to claim 6 and one or two surface layers.
8. A container comprising the resin layer according to claim 6.
9. A container comprising the laminate of claim 7.
10. An article comprising the container and contents of claim 8 or 9.
Citation Information
Patent Citations
Plastic bottle
JP1996244747A
Modified polypropylene resin foam, laminated foam, and molding prepared therefrom
JP1998060144A
Crystalline polypropylene resin composition and injection-molded product obtained from the same
JP2009275117A
Laminated sheets and food containers
JP2021037748A
Spray-drying catalysts containing germanium-bridged bis-biphenyl-phenoxy organometallic compounds for producing ethylene-based copolymers - Patent Application 20070122999
JP2023528188A